MATHGO - 1ª COMPETIÇÃO - Tossi, Lucas Fernando Vieira; Padoin, Edson Luiz; Mendonça, Barbara Gündel (Salão do Conhecimento, 2019)
Projeto de extensão aprovado no edital CNPQ - Semana Nacional de Ciência e Tecnologia Processo n°: 440264/2018-9